2000
DOI: 10.1001/archopht.118.8.1066
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Melanoma Death Rates by Anatomic Site After Proton Beam Irradiation for Uveal Melanoma

Abstract: Background: Ciliary body location is an established prognostic factor for metastasis-related death from uveal melanoma. We evaluated alternative approaches for classifying this covariate when constructing predictive models of patient survival. Methods and Design: The analyses were based on a consecutive series of 1848 primary choroidal and/or ciliary body melanoma patients treated with proton beam irradiation (70 cobalt gray equivalent in 5 fractions) at the Harvard Cyclotron Laboratory, Boston, Mass, between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…The postbrachytherapy follow up included A-scan and B-scan ultrasonography and a clinical examination (including metastatic evaluation) 3 months after the surgery and every 6.6 (0.3) (mean (SE)) months thereafter (a total of 1001 examinations). Each patient was examined on average 5.6 times (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Thirty three of the 147 patients died during the…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The postbrachytherapy follow up included A-scan and B-scan ultrasonography and a clinical examination (including metastatic evaluation) 3 months after the surgery and every 6.6 (0.3) (mean (SE)) months thereafter (a total of 1001 examinations). Each patient was examined on average 5.6 times (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Thirty three of the 147 patients died during the…”
Section: Resultsmentioning
confidence: 99%
“…8 9 Thus, it is important to define clinical factors predictive of metastatic spread. Such unfavourable prognostic parameters include a larger tumour diameter, 10 a faster growing tumour, 11 presence of extrascleral growth, tumour margin location anterior to the equator of the eye, 12 ciliary body involvement, 13 older age, 10 male sex, 10 tumour induced glaucoma, 14 and specific microvascular patterns 10 15 which can be assessed clinically either by confocal indocyanine green angiography [16][17][18] or ultrasound backscatter parameters. 19 We have previously shown that, following brachytherapy, larger tumours shrink significantly faster than smaller ones.…”
mentioning
confidence: 99%
“…As in proton therapy, single fractions in the range 14 to 16 Gy are used to treat ocular melanoma [e.g., see ref. 35], we chose to examine the effects on cells of a single acute dose of 20 Gy of proton beams. To obtain comparable effects with gamma, 40 Gy had to be used.…”
Section: Manymentioning
confidence: 99%
“…In our study, 48% of the patients had a tumor height above 8 mm or a basal diameter above 16 mm (COMS size large). Another important factor is that most of our tumors were located anterior to the equator, and 35% had involvement of the ciliary body, which is a well-known predictor of poor prognosis [16,18,19,20]. …”
Section: Discussionmentioning
confidence: 99%